A new algorithm for the discrimination of actinic keratosis from normal skin and squamous cell carcinoma based on in vivo analysis of optical properties by high‐definition optical coherence tomography. (17th June 2016) - Boone, M.A.L.M.; Suppa, M.; Marneffe, A.; Miyamoto, M.; Jemec, G.B.E.; Del Marmol, V.
Abstract: Background: High‐definition optical coherence tomography (HD‐OCT) features of actinic keratosis (AK) may aid in its diagnosis and therapeutic strategy. A diagnostic algorithm permitting discrimination of AK from squamous cell carcinoma (SCC) and normal skin has been proposed. However, diagnostic accuracy strongly depends on the experience of physicians. In two recent studies, it was demonstrated that HD‐OCT permits to quantify in vivo optical properties such as light attenuation in intrinsic ageing skin, in melanocytic lesions and in basal cell carcinoma. This approach seems to permit a semiautomated classification of lesions easier to handle by non‐experts. Objectives: The aim of this paper was to quantify in vivo optical properties of facial located AK/SCC lesions, such as light attenuation, by HD‐OCT. Additional objectives were to determine the best critical value of these optical properties for discrimination of AK from SCC and from normal sun exposed skin and to subdifferentiate AKs. Methods: The technique of semi‐log plot has been implemented on HD‐OCT signals. This permitted the in vivo measurement of OCT signals coming from the skin entrance up to the superficial reticular dermis. Moreover, relative attenuation factor (μ raf ) at different skin layers (1–3) could be determined. Results: Optical properties with high diagnostic accuracy (DA) and high negative predictive values (NPV) could be defined permitting the differentiation between normal skin, non‐Bowenoid AK without follicular involvement, non‐Bowenoid AK with follicular involvement, Bowenoid AK, hypertrophic and lichenoid form of AK and squamous cell carcinoma. Conclusion: HD‐OCT seems to enable the combination of in vivo morphological analysis of cellular and 3D microarchitectural structures with in vivo analysis of optical properties of tissue scatterers in AK/SCC lesions and normal sun‐exposed skin. In vivo HD‐OCT analysis of optical properties permits AK discrimination from SCC and AK subdifferentiation with higher accuracy than in vivo HD‐OCT analysis of morphology alone.